Characterization of the refractive index in gradient-index elements - Wychowaniec, Marek; Litwin, Dariusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The paper is focused on measurement techniques of gradient-index elements particularly useful for slightly inhomogeneous glasses from small laboratory melts. A construction of the measurement cuvette and dependence of the refractive index of an immersion liquid on its parameters is discussed. The dependence of the refractive index of α-bromonaphtalene on temperature for λ = 0.6328 μm is described. A measuring method of the refractive index profile of gradient-index elements is presented.
Optica Applicata, Vol. 38, 2008, nr 3, s. 609-619
Keywords: optyka; GRIN lenses measurements; refractive index measurement; GRIN glass